Evaluation and Analysis of Lightweight Concrete (LWC) Manufacturing and Applications - Amenah E. Mohammed Redha (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2019)
This paper presents the evaluation and analysis of LWC) manufacturing and applications. Clear comparisons of different LWC types according to the physical specifications and properties lead to accurate selection of concrete type depending on the conditions surrounding the buildings projects. The widely used of LWC in all over the world is approaching researchers to seriously consider finding new techniques to produce more resistant varieties nearby conditions of construction projects. The LWC types are more sustainable than burnt brick due to its providing high densities and better insulation. This work has been carried out the deep discussion and comparison between the properties of fly ash, AAC and CLC concrete types. The advantage of aerated lightweight concrete compared with traditional concrete is present in advance strength to weight ration, less thermal expansion coefficient and high insulation of sound. The classified of aerated lightweight concrete into foamed and autoclaved concrete has attention in the suggested mixture. By maintain the density as constant parameter, their load carrying capacity in compression, water absorption and thermal insulation are to be tabulated and concluded by their performance.